ANALYSIS OF THE INFLUENCE OF VESSEL DENSITY ON THE COMPOSITION, LOCALIZATION AND PERCENTAGE OF DAMAGED VESSELS IN THE TISSUE OF MALIGNANT TUMORS IN BREAST CANCER IN MEN - Munira X. Norbekova; Uktam M. Kurbankulov; Lola T. Alimxodjaeva; Shirina A. Valijonova (Scholar Express Journals, 2023)
Recently, special attention has been paid to the study of vascular density and its significance during the course of the disease in patients with BC. It was found that with the development of metastases, the density of blood vessels in the future was twice as high as compared with clinically positive processes. Their high relative level was noted in aggressive malignant tumors in patients with breast cancer.
Keywords: Breast cancer; vascular density